Cercarial behaviour alters the consumer functional response of three‐spined sticklebacks. Issue 4 (8th February 2021) - Born‐Torrijos, Ana; Paterson, Rachel A.; van Beest, Gabrielle S.; Vyhlídalová, Tereza; Henriksen, Eirik H.; Knudsen, Rune; Kristoffersen, Roar; Amundsen, Per‐Arne; Soldánová, Miroslava
Abstract: Free‐living parasite life stages may contribute substantially to ecosystem biomass and thus represent a significant source of energy flow when consumed by non‐host organisms. However, ambient temperature and the predator's own infection status may modulate consumption rates towards parasite prey. We investigated the combined effects of temperature and predator infection status on the consumer functional response of three‐spined sticklebacks towards the free‐living cercariae stages of two common freshwater trematode parasites ( Plagiorchis spp., Trichobilharzia franki ). Our results revealed genera‐specific functional responses and consumption rates towards each parasite prey: Type II for Plagiorchis spp. and Type III for T . franki, with an overall higher consumption rate on T. franki . Elevated temperature (13°C) increased the consumption rate on Plagiorchis spp. prey for sticklebacks with mild cestode infections (<5% fish body weight) only. High consumption of cercarial prey by sticklebacks may impact parasite population dynamics by severely reducing or even functionally eliminating free‐living parasite life stages from the environment. This supports the potential role of fish as biocontrol agents for cercariae with similar dispersion strategies, in instances where functional response relationships have been established. Our study demonstrates how parasite consumption by non‐host organisms may be shaped by traits inherent to parasite transmission and dispersal, and emphasises the need to consider free‐living parasite life stages as integral energy resources in aquatic food webs. Abstract : This article provides the first study investigating the consumption of two common freshwater trematode parasites by a non‐host fish species, the three‐spined stickleback, examining the combined effects of temperature and predator infection status on the consumer functional response